أثر التمويل الاجتماعي الإسلامي في التمكين الاقتصادي لعلاج الهجرة غير النظامية في مالي - Bilaly Sangare (İstanbul Sabahattin Zaim Üniversitesi, 2024)
Bu çalışma, İslami sosyal finansı, ekonomik ve sosyal güçlenmeye yardımcı olan ve Mali'deki düzensiz göçün ele alınmasına katkıda bulunan bir finansman mekanizması olarak incelemeyi amaçlamaktadır. Araştırmacı, konu ile ilgili kitap ve yayınları kullanarak tanımlayıcı ve analitik bir yaklaşım izlemiştir. Çalışmada, finansman araçlarının çeşitliliği ve halkın ihtiyaçlarına uyum sağlaması nedeniyle İslami sosyal finansın Mali'deki Düzensiz göçle mücadelede uygun bir çözüm olduğu da dahil olmak üzere çeşitli sonuçlara ulaşılmıştır. Mali Mali toplumu çeşitli projelerin finansmanında bundan yararlanabilmesi ve bu projelere ilişkin verilerin elde edileceği sistemlerin kurulması için diğer İslami sosyal finansman araçları.

This study aims to study Islamic social finance as a financing mechanism that helps in economic and social empowerment, which in turn contributes to addressing irregular migration in Mali. The researcher followed the descriptive and analytical approach, using books and publications related to the subject. The study reached several results, including that Islamic social finance is an appropriate solution to confront Irregular migration in Mali due to the diversity of its financing tools and their adaptation to the requirements of the people. Institutions must be established that supervise zakat, Wakf, spending and other Islamic social financing tools so that the Malian society can benefit from it in financing various projects and setting up systems through which data on these projects is obtained.
Mali'de düzensiz göçe karşı islami sosyal finansın ekonomik güçlenmeye etkisi
THE IMPACT OF ISLAMIC SOCIAL FINANCE ON ECONOMICEMPOWERMENT AGAINST IRREGULAR MIGRATION IN MALI
Keywords: İslami sosyal finans; ekonomik güçlenme; düzensiz göç; göçmen; Islamic Social Finance; Economic Empowerment; İrregular Migration; Migrant.; التمويل الاجتماعي الإسلامي; التمكين الاقتصادي; هجرة غيرالنظامية; المهاجر